Attic red-figure kylix (cup) - Followers of Douris: Unascribed
Inside: Hercules in the cup which Helios (the sun) loaned him, sailing toward the Island of Erytheia where he will attack Geryon. Outside: duel between Achilles and Hector, in the presence of Apollo and Athena (repeated on both sides).